Alpha meditation: an introduction - Mohamed Rafee, A S (Sixthsense Publications, Chennai, 2015)
The author, Nagore Rumi, has been teaching Alpha Meditation for over a decade. Thousands of people have practiced it and benefited from it. This book is the first of its kind in Tamil. However, to reach a wider audience, it has also been written in English. It is certain to benefit both those in poor health and enthusiastic readers. Alpha Meditation offers numerous benefits, including improved health, wealth, academic success, employment opportunities, business growth, and solutions to long-standing family problems. It can be likened to discovering a magical lamp within yourself.
Keywords: Alpha meditation